A "practice turn" for global public relations: an alternative approach. Issue 1 (2nd February 2015) - Rittenhofer, Iris; Valentini, Chiara
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to review recent literature on global public relations in order to scrutinize how contemporary transformations are conceptualized in the field, and what this means for the understanding of public. Design/methodology/approach – The authors offer a critical analysis and discussion of recent publications in order to explore the nexus of "public", "culture" and "global", questioning whether the increased interest in a specific understanding of culture actually contributes to the field's ability to deal with complex and transforming publics in a meaningful manner. Findings – The majority of global public relations literature applies redundant understandings of globalization. It attaches prime importance to the concept of culture and contributes little to the understanding of transforming publics. Few scholars acknowledge the limitations of using "culture" for the definition of publics in global contexts. Alternative approaches to understanding "publics" in global public relations research and practice are hardly offered. Research limitations/implications – The findings imply that global public relations research would benefit from abandoning monolithic social science categories and from working transdisciplinary in order to refine its understanding of contemporary societal and social transformations and their implications for the understanding of public and relationship building. Practical implications – The discussion indicates that public relations practitioners could benefit from reorienting their understanding of publics in globalizing societies in order to build and nourish mutually beneficial relationships. The authors apply the insight into contemporary business practices to offer public relations practitioners a starting point for reorientation. Originality/value – The authors contribute to global public relations scholarship with an alternative approach to the understanding of transforming publics which merges the spatial turn and the practice turn known from wider humanities and social science research, and relevant business practices.